Allosteric role of the amino-terminal A/B domain on corticosteroid transactivation of gar and human glucocorticoid receptors. Issue 154 (November 2015) - Oka, Kaori; Hoang, Andree; Okada, Daijiro; Iguchi, Taisen; Baker, Michael E.; Katsu, Yoshinao
Highlights: A–B domain regulates activation of gar GR. Gar A–B domain regulates activation of human GR. A–B domain allosteric activity evolved before separation of fish and tetrapods. Abstract: We studied the role of the A/B domain at the amino terminus of gar ( Atractosterus tropicus ) and human glucocorticoid receptors (GRs) on transcriptional activation by various glucocorticoids. In transient transfection assays, dexamethasone [DEX] and cortisol had a lower half-maximal response (EC50) for transcriptional activation of full length gar GR than of human GR. Both GRs had similar responses to corticosterone, while 11-deoxycortisol had a lower EC50 for gar GR than for human GR. In contrast, constructs of gar GR and human GR consisting of their hinge (D domain), ligand binding domain (LBD) (E domain) fused to a GAL4 DNA-binding domain (DBD) had a higher EC50 (weaker response) for all glucocorticoids. To study the role of the A/B domain, which contains an intrinsically disordered region, we investigated steroid activation of chimeric gar GR and human GR, in which their A/B domains were exchanged. Replacement of human A/B domains with the gar A/B domains yielded a chimeric GR with a lower EC50 for DEX and cortisol, while the EC50 increased for these steroids for the human A/B-gar C/E chimera, indicating that gar A/B domains contributes to the lower EC50 of gar GR for glucocorticoids. Our data suggests that allosteric signaling between the A/B domains and LBD influences transcriptional activation of human and gar GR by different steroids, and this allosteric mechanism evolved over 400 million years before gar and mammals separated from a common ancestor.